If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3yandx + -2y = 4 Reorder the terms: -3adnxy + x + -2y = 4 Solving -3adnxy + x + -2y = 4 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1x' to each side of the equation. -3adnxy + x + -1x + -2y = 4 + -1x Combine like terms: x + -1x = 0 -3adnxy + 0 + -2y = 4 + -1x -3adnxy + -2y = 4 + -1x Add '2y' to each side of the equation. -3adnxy + -2y + 2y = 4 + -1x + 2y Combine like terms: -2y + 2y = 0 -3adnxy + 0 = 4 + -1x + 2y -3adnxy = 4 + -1x + 2y Divide each side by '-3dnxy'. a = -1.333333333d-1n-1x-1y-1 + 0.3333333333d-1n-1y-1 + -0.6666666667d-1n-1x-1 Simplifying a = -1.333333333d-1n-1x-1y-1 + 0.3333333333d-1n-1y-1 + -0.6666666667d-1n-1x-1 Reorder the terms: a = -0.6666666667d-1n-1x-1 + -1.333333333d-1n-1x-1y-1 + 0.3333333333d-1n-1y-1
| (3x-5x+2)+(3x-5)= | | 1/x^-1/6 | | 8x+2=6x+28 | | -x+8y=23 | | x^2-24x+2=0 | | x-3yandx-2y=4whatisx | | 2[w-(2w+20)+16]=2(w+4) | | -x^2+37x-312=0 | | 3(y-4)=5(y+4) | | V=4/3pi103 | | (2x+4)+2x=180 | | V=4/3pir3 | | H/3=3.4 | | 2x^3-3x^2-36x+54=0 | | 10x+8-5=-3(2x+5) | | 4/3pir3 | | x^2+2p+1=2(p-1)x | | -5w-8=-2(w+7) | | 1x+60= | | -13.53=-3h | | -7=-7u+3(u+3) | | 31000/1.5 | | 6x-2+9x=5x+3-7x | | 6x+13=5x+6 | | 0.40x-1.20=0.15x+0.80 | | H/3=-0.11 | | 12x^2-228x+741=0 | | 7x-2(x-1)=3x-8+x+10 | | 12u=28+5u | | 18y+12= | | (m^2-m+3)+(m-1)= | | 2x+11=5(x+1) |